The Sarcophagidae (Insecta: Diptera) described by Chien-ming Chao and Xue-zhong Zhang - Zhang, Dong; Zhang, Ming; Li, Zijuan; Pape, Thomas (Zootaxa, 2015)
The twenty-nine species-group names of Sarcophagidae proposed by Chien-ming Chao and Xue-zhong Zhang are reviewed. Of these names, twenty-four are available, while five are unavailable nomina nuda. Of the twenty-four available names, nine are considered valid, fifteen as invalid: thirteen junior synonyms, one unnecessary replacement name and one junior primary homonym. Holotypes of all species, and allotypes when available, are photographed and the species redescribed based on the type material. Eight new synonyms are proposed: Miltogramma tibita Chao & Zhang, 1988, syn. n. of Miltogramma taeniata Meigen, 1824; Sphenometopa luridimacula Chao & Zhang, 1988, syn. n. of Sphenometopa stackelbergiana Rohdendorf, 1967; Sphenometopa mesomelaenae Chao & Zhang, 1988, syn. n. of Sphenometopa stelviana (Brauer & Bergenstamm, 1891); Sphenometopa altajica Rohdendorf, 1971, syn. n. of Sphenometopa stelviana (Brauer & Bergenstamm, 1891); Sarcophila mongolica Chao & Zhang, 1988, syn. n. of Sarcophila latifrons (Fallén, 1817); Wohlfahrtia brevicornis Chao & Zhang, 1996, syn. n. of Wohlfahrtia grunini Rohdendorf, 1969; Wohlfahrtia hirtiparafacialis Chao & Zhang, 1996, syn. n. of Wohlfahrtia magnifica (Schiner, 1862); and Wohlfahrtiodes mongolicus Chao & Zhang, 1988, syn. n. of Asiosarcophila kaszabi Rohdendorf & Verves, 1978. The genus Asiosarcophila Rohdendorf & Verves, 1978 is herewith reported from China for the first time, along with the five species A. kaszabi, M. taeniata, S. stackelbergiana, S. stelviana and W. grunini.